1996
DOI: 10.1897/1551-5028(1996)015<1375:tagrol>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic and Genotoxic Responses of Larval Chironomus Salinarius Group (Diptera: Chironomidae) to Contaminated Sediment

Abstract: Abstract-Chironomids are important indicators of the effects of sediment-bound contaminants. However, cause-effect relationships between contaminant exposure and stress-related indicators other than growth and survival have not been demonstrated. In the laboratory, we conducted 10-d exposures of Chironomus salinarius group Kieffer larvae to mixtures of contaminated (Trenton Channel, Detroit River, MI) sediment diluted with uncontaminated, formulated sediment (sand, sculptor's clay, and potting soil) in ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Essential for cellular maintenance, NORs are sites for high transcription (Hudson & Ciborowski 1996). The level of transcription is related to variations in the protein requirements of the cells.…”
Section: The Salivary Gland Polytene Chromosomes Of Chironomids and Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential for cellular maintenance, NORs are sites for high transcription (Hudson & Ciborowski 1996). The level of transcription is related to variations in the protein requirements of the cells.…”
Section: The Salivary Gland Polytene Chromosomes Of Chironomids and Tmentioning
confidence: 99%
“…In the majority of cells of a salivary gland, the NOR occurs at the highest activity during the 6-7 th phase of the IV larval stage (Kiknadze 1976(Kiknadze , 1978. Variations of the diameter of the NOR were measured by Hudson and Ciborowski (1996), who found that the diameters in larvae living in a heavily polluted sediment (from Trenton Channel, Detroit), were shorter than the diameters in control larvae. After acute 10 mM Cd treatment, a decrease in the activity of NOR was observed by Planello et al (2007), who used rDNA immunofluorescent probes and Northern blot analysis on total RNA.…”
Section: The Salivary Gland Polytene Chromosomes Of Chironomids and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…They ap pear to be good indicators of sediment quality (HUDSON and CIBOROWSKI 1996). Even more, a correlation between several larval morphological deformities and long term chronic toxicity has been observed (WARWICK 1990) and they were proposed as a suitable indicator of pollution.…”
Section: Introductionmentioning
confidence: 99%
“…(68). The polytene chromosomes of some insect species (chironomids, Drosophila) appear to be promising tools to assess the genotoxic effects of environmental contaminants (79)(80)(81)(82).…”
Section: Invertebrates In Laboratory Toxicology Testingmentioning
confidence: 99%